Multicore‒shell nanocomposite formed by encapsulation of WO3 in zeolitic imidazolate framework (ZIF-8): As an efficient photocatalyst. Issue 5 (October 2019) - Malik, Ankur; Nath, Mala
Graphical abstract: Highlights: I n situ encapsulation of WO3 NPs in ZIF-8 resulted WO3 @ZIF-8. WO3 @ZIF-8 photocatalytically degrades ( ca. 99.2%) methylene blue. Scavenger analysis confirmed major role of OH and h + (ROS) in photo- degradation. The degraded by-products of MB have been analysed by GC–MS. Abstract: Modified zeolitic imidazolate framework (ZIF-8) with encapsulated WO3 nanoparticles have yielded three multicore‒shell nanocomposites by in situ encapsulation of 150 (abbreviated as WZ-1), 300 (abbreviated as WZ-2) and 500 (abbreviated as WZ-3) μL suspension of WO3 NPs in methanol in ZIF-8 matrix at room temperature. They have been characterized by powder X-ray diffraction (PXRD), X-ray photoelectron spectroscopy (XPS), Fourier transform-infra-red (FT-IR) spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Encapsulation of WO3 NPs was evidenced by TEM, SAED and ultraviolet diffuse reflectance spectroscopy (UV-DRS). The composites have lower band gap with higher light absorbance compared to ZIF-8 due to the shift in the micro-environment of ZIF-8 framework. Particle size of encapsulated WO3 NPs within the matrix of ZIF-8 was found 9.56 ± 1.29 nm. ZIF-8 and WO3 NPs@ZIF-8 are highly thermally stable up to 397 °C and in the range of 450–650 °C ZIF-8 shell gets decomposed and converted into oxide. Application of WO3 NPs@ZIF-8 towards photodegradation of methylene blue (MB) dye has been investigated by varying the amount of catalyst (5, 10 and 15 mg) and dye concentration (5, 10 and 15 mg L −1 ) at different pH (3–11). WZ-2 (10 mg) exhibits excellent photocatalytic activity; degrades 99.2% MB (5 mg L −1 ) at pH. Further, WZ-2 can be reutilized up to five cycles with almost same efficiency and remains unchanged. Therefore, it can be utilized as an efficient photocatalyst for remediation of environmental pollution.